Analisis Proses Operasional Pengecekan Layak Terbang Cargo Handling - Albert Kurniawan Purnomo; Yahya Zakaria; Desta Sulaesih Mursyidah; Utari Kartika Sari (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
Restrictions on passengers during the Covid-19 pandemic at airports aim to reduce the rate of transmission of Covid. However, this actually increases the growth of freight forwarding which has an impact on increasing cargo. At the cargo terminal there is no x-ray which functions to check cargo and post. Therefore, cargo and post must be checked by the regulated agent outside the line 1 area. Several incidents have been found at the regulated agent which may have an impact on losses. This study aims to determine the procedure for checking outgoing cargo at the regulated agent, to find out the problems that occur in checking outgoing cargo at the regulated agent, and to find out solutions to overcome problems in checking outgoing cargo at the regulated agent. This study uses qualitative research methods with more data collection techniques on participant observation, in-depth interviews and documentation conducted on cargo agent and regulated agent. The results of the study prove that all research objectives, namely procedures for checking outgoing cargo at the regulated agent, problems that occur in checking outgoing cargo at the regulated agent, and solutions to overcome problems in checking cargo outgoing at the regulated agent have been identified. Furthermore, practical conclusions and suggestions will be discussed in more depth in this study.